Time-Resolved Investigation of Molecular Components Involved in the Induction of NO3– High Affinity Transport System in Maize Roots - Pii, Youry; Alessandrini, Massimiliano; Dall’Osto, Luca; Guardini, Katia; Prinsi, Bhakti; Espen, Luca; Zamboni, Anita; Varanini, Zeno (Frontiers in Plant Science, 2016)
The induction, i.e. the rapid increase of nitrate (NO3-) uptake following the exposure of roots to the anion, was studied integrating physiological and molecular levels in maize roots. Responses to NO3- treatment were characterized in terms of changes in NO3- uptake rate and plasma membrane (PM) H+-ATPase activity and related to transcriptional and protein profiles of NRT2, NRT3 and PM H+-ATPase gene families. The behaviour of transcripts and proteins of ZmNRT2s and ZmNRT3s suggested that the regulation of the activity of inducible high-affinity transport system (iHATS) is mainly based on the transcriptional/translational modulation of the accessory protein ZmNRT3.1A. Furthermore, ZmNRT2.1 and ZmNRT3.1A appear to be associated in a ∼ 150 kDa oligomer. The expression trend during the induction of the 11 identified PM H+-ATPase transcripts indicates that those mainly involved in the response to NO3- treatment are ZmHA2 and ZmHA4. Yet, partial correlation between the gene expression, protein levels and enzyme activity suggests an involvement of post-transcriptional and post-translational mechanisms of regulation. A nondenaturing Deriphat-PAGE approach allowed demonstrating for the first time that PM H+-ATPase can occur in vivo as hexameric complex together with the already described monomeric and dimeric forms.